Patient-reported outcomes with belantamab mafodotin, bortezomib, and dexamethasone versus daratumumab, bortezomib, and dexamethasone in patients with relapsed or refractory multiple myeloma (DREAMM-7): results from a phase 3, open-label, randomised controlled trial - Hungria, Vania; Hus, Marek; Fu, ChengCheng; Zherebtsova, Vera; Ward, Christopher; Ho, P Joy; Mikulski, Damian; Muronova, Ludmila; Cerchione, Claudio; Loubert, Angely; Bunod, Laurine; M'Hari, Manal; et al. (The Lancet. Haematology, 2025)
BACKGROUND: Belantamab mafodotin, bortezomib, and dexamethasone showed significant progression-free survival benefit compared with daratumumab, bortezomib, and dexamethasone in relapsed or refractory multiple myeloma in the phase 3 DREAMM-7 study. We aimed to evaluate the effect of belantamab mafodotin, bortezomib, and dexamethasone compared with daratumumab, bortezomib, and dexamethasone on health-related quality of life (HRQOL) using various patient-reported outcomes in patients who participated in DREAMM-7. METHODS: This phase 3, open-label, randomised controlled trial, done at 142 hospitals in 20 countries included adult patients aged 18 years or older with relapsed or refractory multiple myeloma who received at least one previous line of therapy and progressed during or after their most recent treatment and had an Eastern Cooperative Oncology Group performance status of 0 to 2. Eligible patients were randomly assigned (1:1) by a central interactive response technology system to receive intravenous belantamab mafodotin (2·5 mg/kg once on day 1 of each 21-day cycle) or intravenous daratumumab (16 mg/kg once a week in cycles 1-3, every 3 weeks in cycles 4-8, and every 4 weeks in cycle 9 and beyond). Patients in both treatment groups also received subcutaneous bortezomib (1·3 mg/m2 on days 1, 4, 8, and 11 of 21-day cycles) and oral or intravenous dexamethasone (20 mg on the day of and day after bortezomib administration) for the first 8 cycles. Treatment continued until progressive disease, unacceptable toxic effects, withdrawal of consent, or death (whichever occurred first). Patient-reported outcomes were secondary and exploratory objectives. Secondary patient-reported outcome endpoints were change from baseline in HRQOL, as measured by the European Organisation for Research and Treatment of Cancer (EORTC) QLQ-C30 and EORTC QLQ-MY20, and maximum postbaseline score for each item attribute on the Patient-Reported Outcomes version of the Common Terminology Criteria for Adverse Events (PRO-CTCAE). Exploratory patient-reported outcome endpoints included changes from baseline in symptoms and related effects as measured by Ocular Surface Disease Index (OSDI), change from baseline in FACT-GP5 score, and change from baseline in the EQ-5D VAS. EORTC QLQ-C30, EORTC QLQ-MY20, and FACT-GP5 scores were analysed in the intention-to-treat population, and PRO-CTCAE and OSDI vision-related functioning scores were analysed in the safety population (patients who received at least one dose of treatment). Results were summarised using descriptive statistics. Least-squares mean changes from baseline were estimated using a restricted maximum likelihood-based mixed model. This study was registered with ClinicalTrials.gov, NCT04246047, and is ongoing. FINDINGS: Between May 7, 2020, and June 28, 2021, 494 patients were included in the intention-to-treat population of the DREAMM-7 study (median follow-up 28·2 months, IQR 14·6-31·4) and were randomly assigned to either belantamab mafodotin, bortezomib, and dexamethasone (n=243) or daratumumab, bortezomib, and dexamethasone (n=251). 222 (45%) of 494 patients were female and 272 (55%) were male. The mean age in the total study population was 64·0 years (SD 9·80). Most patients were White (409 [83%] of 494), Asian (61 [12%]), or Black or African American (20 [4%]). Patients in both groups had stable mean EORTC QLQ-C30 and QLQ-MY20 scores over time. At each timepoint, most patients reported stable or improved scores in the global health status/quality of life (64 [56%] of 115 patients to 85 [75%] of 114 patients in the belantamab mafodotin group and 105 [51%] of 207 patients to 156 [65%] of 240 patients in the daratumumab group), role functioning (103 [53%] of 196 patients to 77 [68%] of 114 patients in the belantamab mafodotin group and 99 [50%] of 197 patients to 92 [69%] of 134 patients in the daratumumab group), and physical functioning domains (132 [66%] of 201 patients to 101 [77%] of 131 patients in the belantamab mafodotin group and 115 [58%] of 197 patients to 102 [76%] of 134 patients in the daratumumab group) of the EORTC QLQ-C30 and of the disease symptom domain scores of the EORTC QLQ-MY20 (79 [72%] of 109 patients to 95 [83%] of 115 patients in the belantamab mafodotin group and 126 [66%] of 190 patients to 164 [74%] of 221 patients in the daratumumab group). Most patients in the belantamab mafodotin group (155 [77%] of 202 to 79 [96%] of 82) and the daratumumab group (155 [86%] of 181 to 60 [100%] of 60) reported being "not at all," "a little," or "somewhat" bothered by treatment side-effects at each visit, as determined by the FACT-GP5. INTERPRETATION: HRQOL was generally maintained or improved over time with belantamab mafodotin, bortezomib, and dexamethasone treatment. Our findings, in conjunction with previously reported clinical benefits, support the use of belantamab mafodotin as a potential new standard of care in relapsed or refractory multiple myeloma. FUNDING: GSK. TRANSLATIONS: For the Polish and Spanish translations of the abstract see Supplementary Materials section.
Keywords: Antibodies, Monoclonal; mužské pohlaví; hodnocení výsledků péče pacientem; Male; senioři; výsledek terapie; Patient Reported Outcome Measures; Humans; Female; Multiple Myeloma; Antibodies, Monoclonal, Humanized; lidé; Middle Aged; ženské pohlaví; lidé středního věku; mnohočetný myelom; Antineoplastic Combined Chemotherapy Protocols; monoklonální protilátky; kvalita života; Quality of Life; Treatment Outcome; protokoly protinádorové kombinované chemoterapie; dexamethason; dospělí; Dexamethasone; Adult; Bortezomib; humanizované monoklonální protilátky; bortezomib; Aged